2020
DOI: 10.1186/s12964-020-0523-3
|View full text |Cite|
|
Sign up to set email alerts
|

Cytochrome P450 1A1 enhances inflammatory responses and impedes phagocytosis of bacteria in macrophages during sepsis

Abstract: The hydroxylase cytochrome P450 1A1 (CYP1A1) is regulated by the inflammation-limiting aryl hydrocarbon receptor (AhR), but CYP1A1 immune functions remain unclear. We observed CYP1A1 overexpression in peritoneal macrophages (PMs) isolated from mice following LPS or heat-killed Escherichia. coli (E. coli) challenge. CYP1A1 overexpression augmented TNF-α and IL-6 production in RAW264.7 cells (RAW) by enhancing JNK/AP-1 signalling. CYP1A1 overexpression also promoted 12S-hydroxy-5Z,8Z,10E,14Z-eicosatetraenoic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 56 publications
0
29
0
Order By: Relevance
“…These findings suggest that repeated administration of N-ZnO is more likely to affect immune response than B-ZnO. It was reported that CYP1A1 was highly expressed in inflammatory macrophages and the mice skin, inducing release of pro-inflammatory mediators and immune cell activation [50,51]. Hence, signaling pathway involving inflammation response can be a target for further mechanistic toxicity study.…”
Section: Discussionmentioning
confidence: 92%
“…These findings suggest that repeated administration of N-ZnO is more likely to affect immune response than B-ZnO. It was reported that CYP1A1 was highly expressed in inflammatory macrophages and the mice skin, inducing release of pro-inflammatory mediators and immune cell activation [50,51]. Hence, signaling pathway involving inflammation response can be a target for further mechanistic toxicity study.…”
Section: Discussionmentioning
confidence: 92%
“…It has been reported that genes of the CYP450 family varied similarly in the liver of experimental mice infected with E. multilocularis [ 30 ]. Moreover, a recent study demonstrated that members of the CYP family CYP1A could enhance inflammatory responses [ 48 ]. This aligns with the results of our previous study showing several upregulated miRNAs, which are related to NF-KB inflammation pathways, and play important roles in the response of intestinal tissue to E. granulosus infection in sheep with resistant haplotypes [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the roles of Nrf2 in macrophage polarization remain controversial. In addition, it has been reported that 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD), an AhR-related inducer of the cytochrome P450 1A1 (CYP1A1), enhances the DNA binding activity of nuclear factor-kappaB (NF-κB) and activator protein-1 (AP-1) in macrophages during inflammation or sepsis 50 , 51 . In summary, the precise mechanisms by which AhR regulates macrophage polarization, especially in CaOx nephrocalcinosis, remain ambiguous and require further investigation.…”
Section: Discussionmentioning
confidence: 99%